Control of Irrigation Systems by Using PIC Microcontroller Connencted to Telephone Lines - Gedikpinar, Mehmet; Cavas, Mehmet (Gazi Univ, 2005)
In this study, it has been aimed to control irrigation systems with instructions given on the telephone lines by taking into consideration of agricultural fields and activities in our country, to achieve this, a control circuit has been designed.
Keywords: PIC Microcontroller; Irrigation Systems; Remote Control